Contribution to the study of F.E. IX: Tannic acid - Suñé, José María; Díaz, R, Mª.; Gallo, M. (Ars Pharmaceutica (Internet), 1965)
The monograph "Acidum Tannicum" by F.E. IX comparing it with that of the Argentine, Belgian, Brazilian, British, French, German, Swiss, Japanese and Russian pharmacopoeias. Some errors or errata in the text are amended and modifications are proposed based on theoretical considerations and experimental data.